Inhibition of cAMP responsive element binding protein in striatal neurons enhances approach and avoidance responses towards morphine- and morphine withdrawal-related cues - Sanchis-Segura, Carles; Jancic, Dragana; Jimenez-Minchan, Maria; Barco, Angel (Frontiers in Behavioral Neuroscience, 2009)
To investigate the role of cAMP resposive element binding protein (CREB)-dependent gene expression in morphine induced behaviors, we examined bitransgenic mice expressing a dominant and strong inhibitor of the CREB family of transcription factors, A-CREB, in striatal neurons in a regulatable manner. The expression of A-CREB in the striatum enhanced both morphine-induced conditioned place preference and morphine withdrawal–induced conditioned place avoidance. Our experiments thereby support a role for CREB in striatal neurons regulating approach and avoidance responses towards drug-related cues.